The impact of accounting conservatism on financing decisions in Sudan - mohamed adem ali, elsadig; ahmad mehamed harone, Eman (Journal of Research in Finance and Accounting, 2025)
The study aimed to identify the concept of accounting conservatism and bank financing decisions and to clarify the impact of accounting conservatism on bank financing decisions through a field study on a sample of Sudanese banks operating in Elobeid city, Sudan. The study concluded that accounting conservatism helps increase the efficiency and quality of bank financing decisions and also contributes to addressing problems and complaints related to bank financing decisions. The study recommended that banks experiencing difficulties in financing decisions should exercise an appropriate degree of accounting conservatism. Taking into account the quality of financial data, the need for continuous reform of the Sudanese banking system to keep pace with global economic developments.